2021
DOI: 10.1039/d1gc00829c
|View full text |Cite
|
Sign up to set email alerts
|

Solvent extraction in extended hydrogen bonded fluids – separation of Pt(iv) from Pd(ii) using TOPO-based type V DES

Abstract: In this work, the challenging solvent extraction (SX) separation of Pt(IV) from Pd(II) is investigated using non-ionic hydrophobic Type V deep eutectic solvent (DES) incorporating trioctylphosphine oxide (TOPO) as constituent....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…, pH, salinity, temperature, etc .). 113,159,173 Besides, the mechanical studies of the non-ionic type V DESs for metal extraction could be easier in the model systems. Take TOPO-based H(D)ESs for Pt( iv ) extraction as an example, TOPO: l-menthol, TOPO: 1-hexanol, and TOPO: 1-butanol were selected to investigate the interaction between H(D)ESs and PtCl 6 2− in a model system which was prepared by dissolving H 2 PtCl 6 in distilled water with hydrochloric acid.…”
Section: Current Applications Of Des For Metal Recovery and Separatio...mentioning
confidence: 99%
See 4 more Smart Citations
“…, pH, salinity, temperature, etc .). 113,159,173 Besides, the mechanical studies of the non-ionic type V DESs for metal extraction could be easier in the model systems. Take TOPO-based H(D)ESs for Pt( iv ) extraction as an example, TOPO: l-menthol, TOPO: 1-hexanol, and TOPO: 1-butanol were selected to investigate the interaction between H(D)ESs and PtCl 6 2− in a model system which was prepared by dissolving H 2 PtCl 6 in distilled water with hydrochloric acid.…”
Section: Current Applications Of Des For Metal Recovery and Separatio...mentioning
confidence: 99%
“…Some typical type V DESs, including menthol-based, thymol-based and trioctylphosphine oxide (TOPO)-based DESs, were reported to be capable of selective metal extraction, such as In(III), Pt(IV), Pd(II), Fe(III), Cu(II) or Co(II), in the model systems of synthetic aqueous solutions. 86,90,113,159,173 For example, Schaeffer et al (2020) 86 reported that the TOPO-based DESs displayed good selectivity towards Pt 4+ , Pd 2+, and Fe 3+ over other transition metals (i.e., Cu 2+ , Co 2 + , Ni 2+ , and Cr 3+ ) in HCl aqueous solution; the selective separation of Pt(IV) from Pd(II) in HCl solutions could be also achieved by using the TOPO-based DESs extractants (i.e., TOPO : decanoic acid). 173 The extraction and separation of Cu(II) from other transition metals like Co(II) and Ni(II) could use the type V DESs based on menthol or its aromatic counterpart thymol combined with long-chain carboxylic acids.…”
Section: Studies In Model Systemsmentioning
confidence: 99%
See 3 more Smart Citations